European Association for Osseointegration Delphi study on the trends in Implant Dentistry in Europe for the year 2030. Issue 5 (29th April 2019) - Sanz, Mariano; Noguerol, Blas; Sanz‐Sanchez, Ignacio; Hammerle, Christoph H. F.; Schliephake, Henning; Renouard, Frank; Sicilia, Alberto; Cordaro, Luca; Jung, Ronald; Klinge, Bjorn; Valentini, Pascal; et al.
Abstract: Objectives: To assess the potential trends for the year 2030 in dental implant dentistry in Europe using the Delphi methodology. Material and methods: A steering committee and a management team of experts in implant dentistry were created and validated a questionnaire including 60 questions, divided in eight topics. The survey was conducted in two rounds using an anonymous questionnaire, which provided the participants in the second round with the results of the first. Each question had three possible answers, and the results were expressed as percentages. Results: A total of 138 experts were invited to participate in the survey. From all the invited experts, 52 answered in both the first and second rounds. Three different consensus categories were established based on the percentage of agreement: no consensus (<65%); moderate consensus (65%–85%); and high consensus (≥86%). Within the topic categories, a consensus was reached (mainly moderate consensus) for the majority of questions discussed among experts during a face to face consensus meeting. However, consensus was not reached for a small number of questions/topics. Conclusions: About 82% of the questions reached consensus. The consensus points towards a lower number of implants to replace chewing units, with implants surfaces made of bioactive materials with reduced micro‐roughness using mainly customized abutments with polished surfaces and an internal implant–abutment connection (85%). CBCT‐3D technologies will be the main tool for pre‐surgical implant placement diagnosis together with direct digital restorative workflows. There will be an increase in the incidence of peri‐implantitis, although there will be more efficient interventions its treatment and prevention.